The Identifikasi Peran Orang Tua dalam Pembelajaran Selama Masa Pandemi Covid-19 di SMP Negeri Satu Atap Nefotes - Estri Feronike Baun; Yulius Musa Natonis; Maria Loban (Ra'ah: Journal of Sociology of Religion, 2022)
The COVID-19 pandemic affects various aspects of human life, as in the fields of education, health, economy and various other fields. In the field of education, affects the learning process. Learning that was previously carried out in schools directly / face to face, then becomes learning at home. Learning during the pandemic period at home, cannot be separated from the role of parents. Parents have an important roles in supporting and supervising every learning process. The purpose of this study was to identify the role of parents in learning during the COVID-19 pandemic at SMP Negeri Satu Atap Nefotes. The research method used is qualitative research. The data collection method uses structured interviews, non-participant observation, and documentation studies. There are several stages in data analysis, namely data reduction, data display, and conclusion drawing/verification. The results showed that the roles of parents in learning during the COVID-19 pandemic was as educators, as mentors, motivators, and facilitators. Parents also play a role in helping to deal with learning difficulties faced by students/children so that the learning process can take place optimally. Keywords: parents; learning.